Macrophage Activation and M2 Polarization in Wound Bed of Diabetic Patients Treated by Dermal/Epidermal Substitute Nevelia. (December 2022) - Montanaro, Manuela; Meloni, Marco; Anemona, Lucia; Giurato, Laura; Scimeca, Manuel; Izzo, Valentina; Servadei, Francesca; Smirnov, Artem; Candi, Eleonora; Mauriello, Alessandro; Uccioli, Luigi
Clinical evidences have shown good results using dermal/epidermal substitutes (DESs) to treat diabetic foot ulcers. Recent studies suggest that, in addition to their scaffold action, DESs may favor wound healing by influencing wound bed inflammatory cells. This study aims to investigate whether DES may influence the inflammatory infiltrate and macrophages polarization toward a reparative phenotype. Fifteen diabetic patients with chronic foot ulcers have been randomly enrolled: 5 treated only by standard of care, served as control group (CG), and 10 treated with DES composed of type 1 bovin collagen (Nevelia, SYMATESE) considered as test group (TG). A biopsy was taken at baseline (T0) and after 30 days (T1). From bioptic paraffin specimen histological, immunohistochemical, and immunofluorescence analysis was performed. Immunohistochemistry reactions evaluated the number of M1 macrophage (CD38 + ) and M2 macrophage (CD163 + ). TG patients displayed general macrophage activation and their greater polarization toward M2 subpopulation 30 days after DES implant, compared with CG. From T0 to T1 there was a significant decrease of CD38 + (230 ± 42 and 135 ± 48 mm 2, respectively; P < .001) and significant increase of CD163 + (102 ± 21 positive cells/mm 2 and 366 ± 42 positive cells/mm 2, respectively; P < .001). Confocal microscopy confirmed an increase of M2 cells as expressed by the reduced CD68 + /CD163 + ratio. After 6 months of observation 6 patients (60%) of the TG completely healed, while only 1 patient (20%) healed in the CG ( P < .01). The tested DES makes possible to treat diabetic foot ulcers inducing tissue reparative processes through macrophage activation and M2 reparative polarization.